Transnational Da'wah and Migrant Community Empowerment: A Case Study of Pesantren An-Nahdloh in Malaysia - Idan Ramdani (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
This paper explores the dynamics of transnational da'wah and community empowerment through the case of Pesantren An-Nahdloh in Malaysia, a pesantren established by Indonesian Nahdlatul Ulama (NU) migrants. The central question concerns how a pesantren initiated and funded by migrant workers can function as a medium of da'wah and social empowerment beyond national borders. Positioned within the discourse of transnational Islamic movements and grassroots religious communication, this study adopts a qualitative-descriptive method using document analysis and contextual observation. The discussion reveals that the pesantren operates not only as an Islamic educational institution but also as a center for da'wah bil hal addressing social, moral, and educational needs of Indonesian migrant communities. This model demonstrates how da'wah institutions initiated by civil society actors can facilitate cultural resilience, religious moderation, and local empowerment in diaspora settings.